Pengaruh Persepsi Harga, Persepsi Nilai Pelanggan dan Kepercayaan Pelanggan Terhadap Kepuasan Pelanggan - Ega Ellena; Wahyu eko Setianingsih; Ahmad Izzuddin (Jurnal Manajemen DIVERSIFIKASI, 2026)
This research was conducted to determine the influence of price perception, customer value perception and customer trust on customer satisfaction at Seblak King Purwoharjo. This research uses a quantitative method with a purposive sampling method of 98 respondents, using a questionnaire distributed via Google from to Seblak King Purwoharj customers. The data analysis used is multiple linear regression, partial test, and coefficient of determination test (R2). And the results of the analysis using SPSS 27 show that three variables, namely, price perception, customer value perception and customer trust have a significant effect on customer satisfaction at Seblak King Purwoharjo. The results of the determination test (r2) of (43.7%) show the large proportion or percentage contribution of the variables price perception, customer value perception and customer trust to customer satisfaction. Meanwhile (56.3%) was contributed by other variables not included in this research, for example, location, storytelling and so on.